Library Culture Among Students of Bachelor in Public Service and Governance (BPSG) - Malla, Raju; Bhattarai, Pratikshya (Voice of Teacher, 2023)
This study explores Library Culture among students at BPSG of Padmakanya Multiple Campus. The study population comprises 80 students from the 2nd, 4th, 6th, and 7th semesters, with 55 samples selected using stratified random sampling. The questionnaire, structured according to predetermined objectives, serves as the primary research tool. Data collected are analyzed using MS Excel, and the findings are presented through tables, pie charts, and bar diagrams. The analysis indicates that the library is generally clean, tidy, and offers good accessibility and comfortable reading spaces. However, improvements are needed in these areas, along with addressing dissatisfaction in technology integration, book variety, and quality. From the students’ perspective, the library culture at BPSG is found to be unsatisfactory and poor. This is evident in their infrequent library visits, underutilization of available resources, and a lack of awareness regarding library facilities. Several recommendations are provided, emphasizing the necessity for serious consideration and effective measures. These suggestions aim to enhance the library’s physical environment, technological aspects, and book collection. Addressing these concerns will likely contribute to an improved library culture among BPSG students.